Interleukin‐6 neutralization ameliorates symptoms in prematurely aged mice. Issue 1 (3rd January 2021) - Squarzoni, Stefano; Schena, Elisa; Sabatelli, Patrizia; Mattioli, Elisabetta; Capanni, Cristina; Cenni, Vittoria; D'Apice, Maria Rosaria; Andrenacci, Davide; Sarli, Giuseppe; Pellegrino, Valeria; Festa, Anna; Baruffaldi, Fabio; et al.
Abstract: Hutchinson–Gilford progeria syndrome (HGPS) causes premature aging in children, with adipose tissue, skin and bone deterioration, and cardiovascular impairment. In HGPS cells and mouse models, high levels of interleukin‐6, an inflammatory cytokine linked to aging processes, have been detected. Here, we show that inhibition of interleukin‐6 activity by tocilizumab, a neutralizing antibody raised against interleukin‐6 receptors, counteracts progeroid features in both HGPS fibroblasts and Lmna G609G / G609G progeroid mice. Tocilizumab treatment limits the accumulation of progerin, the toxic protein produced in HGPS cells, rescues nuclear envelope and chromatin abnormalities, and attenuates the hyperactivated DNA damage response. In vivo administration of tocilizumab reduces aortic lesions and adipose tissue dystrophy, delays the onset of lipodystrophy and kyphosis, avoids motor impairment, and preserves a good quality of life in progeroid mice. This work identifies tocilizumab as a valuable tool in HGPS therapy and, speculatively, in the treatment of a variety of aging‐related disorders. Abstract : Signs of premature ageing are improved by tocilizumab treatment. A study in a murine model of Hutchinson‐Gilford Progeria shows that neutralization of interleukin 6 preserves motor activity and slows‐down tissue deterioration.